Promosi Objek Wisata di Kecamatan X Koto Singkarak Sumatera Barat - Muhammad Alfansha Agyuri; San Ahdi (Student Research Journal, 2024)
One of the sub-districts in West Sumatra that has tourism potential is X Koto Singkarak. However, due to the lack of promotion, especially in the tourism sector, there are still many people who do not know about the existence of tourism in X Koto Singkarak District. These factors cause the need to produce media in order to promote tourism in X Koto Singkarak District. The best type of media to promote tourism is video. The design of this promotional video will highlight the artificial and natural tourism in the sub-district. This video was published on a number of social media platforms, such as Instagram, Tiktok, and YouTube.